Exploration of Potential Regional Resources for Beef Cattle Farming Development in Java, Indonesia - Widiati, Rini (2015)
National beef production in Indonesia from year to year has been always low compared with the consumer demand, thus it still depend on imports. The purposes of this study were: (1) to identify factors related to the regional resources which support the development of cattle farming, (2) to determine the potential resources for the development of beef cattle farming, and (3) to improve beef cattle development strategy based on potential resources. The location taken were two provinces in Java, namely East Java Province and Special Region of Yogyakarta. Time series data from 2007 to 2012 as variables in this study were taken as each 7 and 4 regency as the samples. These data were analyzed by Multiple Regression Model using Ordinary Least Square method. The stationary test was done before using time series data by unit root test of Augmented Dickey-Fuller (ADF). Dependent variable in the model was beef cattle population in each regency per year.Meanwhile the independent variables were population, number of farmers, price of catle, number of cattle slaughtered, number of cattle that exit from region, number of cattle that enter to region, ride production, corn production, soybean production, cassava production in each region per year and dummy location. The results of this research showed that enhancement of corn and soybean production in a region was potential resource to increase the population of beef catlle.Moreover, the beef cattle price per kg of live weight and number of beef cattle slaughtered in a region need to be considered as the factors for strategies in developing beef cattle farming. Location has significant effect on the beef cattle development.